1986
DOI: 10.1007/bf00266989
|View full text |Cite
|
Sign up to set email alerts
|

The plastome of Citrus. Physical map, variation among Citrus cultivars and species and comparison with related genera

Abstract: A physical plastome map was constructed for Citrus aurantium, and the plastomes of species and cultivars of Citrus and of two Citrus relatives were analysed by Southern blot-hybridisation of labelled total tobacco cpDNA to digests of total Citrus DNA. A resemblance was found between the plastomes of cultivars of C. limon (lemon), C. sinensis (orange), C. aurantium (sour orange), C. paradisii (grapefruit) and C. grandis (pomello). The plastomes of other Citrus types such as mandarin (C. reticulata) and citron (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
0
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 18 publications
9
31
0
2
Order By: Relevance
“…Deng et al (1995) also established 'Interdonato' as quite distinct lemon cultivar. The overall impression of evolution and variability in lemons depicted from 1998; Nicolosi et al, 2000;Abkenar et al, 2004), which is consistent with the previous cpDNA analysis (Green et al, 1986). Apparently, there has not been the same level of divergence at the molecular level as it is phenotypically.…”
Section: Tab 5 Results Of Amova Analysis Of the Three Citrus Speciessupporting
confidence: 75%
“…Deng et al (1995) also established 'Interdonato' as quite distinct lemon cultivar. The overall impression of evolution and variability in lemons depicted from 1998; Nicolosi et al, 2000;Abkenar et al, 2004), which is consistent with the previous cpDNA analysis (Green et al, 1986). Apparently, there has not been the same level of divergence at the molecular level as it is phenotypically.…”
Section: Tab 5 Results Of Amova Analysis Of the Three Citrus Speciessupporting
confidence: 75%
“…Green et al (1986) and Yamamoto and Kobayashi (1996) demonstrated the usefulness of cpDNA analysis of Citrus by restriction fragment length polymorphism (RFLP). This is a very time-, labor-, and cost-consuming method but has high reproducibility and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Organellar restriction fragment length polymorphisms (RFLPs), either conventional or PCR-based, have been used to study phylogenetic relationships of Citrus and its related genera (Green et al, 1986;Nicolosi et al, 2000;Abkenar et al, 2004a). Analysis of chloroplast DNA (cpDNA) variant is especially valuable in phylogenetic and maternal similarity studies of suspected hybrids due to its evolutionary conservatism and predominant uniparental inheritance, maternal in citrus.…”
Section: Introduction Smentioning
confidence: 99%